DUCTILITY OF HIGH PERFORMANCE CONCRETE BEAMS USING SANDSTONE AGGREGATES - Kumar, P.S; Mannan, M.A.; Kurian, V.J. (6th Asia-Pacific & Construction Conference, 2006)
Due to brittle nature, the extensive use of High Performance Concrete (HPC) in flexural members has been limited. An attempt has been made to improve the ductility using crushed sandstone coarse aggregate and partial substitution of crushed sandstone sand as fine aggregate. Tests on the ductility behaviour of reinforced HPC beams under static loading are reported in this study. The beams were made from concrete compressive strength of 74 N/mm2 and 78 N/mm2. The tensile reinforcement ratio varied in the range of 1.34% to 3.14 %. Tests results showed that the ductility indices sharply decreased with increased tension steel ratio. However, at low tension steel ratio the curvature ductility was greater than 3 and it is sufficient to sustain moderate earthquakes. The end rotation of the beam is in the range of 0.028 rad/m to 0.043 rad/m. Substitution of sandstone mineral fillers and silica fume improved the flexural stiffness and rigidity. HPC made with sandstone aggregates provides weaker bond in the interfacial zone with better energy dissipation. Hence, the ductility increased significantly.